Development of an Iberian Chorizo Salted With a Combination of Mineral Salts (Seawater Substitute) and Better Nutritional Profile - Tejada, Luis; Buendía-Moreno, Laura; Álvarez, Elisa; Palma, Agustín; Salazar, Eva; Muñoz, Beatriz; Abellán, Adela (Frontiers in Nutrition, 2021)
The present study evaluated the effect of salt reduction using a seawater substitutes, at the nutritional and mineral composition, its physicochemical, biochemical, microbiological, and sensory characteristics of Iberian chorizo, compared with one elaborated with low salt content (KCl) and another with a normal salt content (CTRL). To this end, three batches of chorizo were prepared [Lot 1: CTRL, 100% NaCl; Lot 2: KCl, 31% NaCl, and Lot 3: SC (Winbi ®), <3% NaCl]. In KCl and SC chorizo lots, values of humidity, salt, and water activity (aw) were significantly lower (P < 0.05) than in the CTRL chorizo. The chorizo with lower salt content presented higher proteolytic activity; with the nutritional declaration “reduced Na content “with Na values 25% lower than the CTRL. In addition, using this combination caused significant effects (P < 0.05) on the mineral composition of chorizo SC, allowing the inclusion of more nutritional and health claims in its labelling under legislation. The partial substitution of NaCl for KCl (31%), caused an increase in the gumminess, chewiness, and hardness of the chorizo. The SC chorizo lost the reddish hue typical of this sausage, although it was the best sensory valued by a panel of consumers. No differences were observed in the microbiological quality of the different batches of chorizo, always fulfilling the legally established microbiological criteria.